Social Studies Teachers' Perceptions of Merdeka Belajar Curriculum through Islam-Based Materials for Madrasah Tsanawiyah in Kudus - Misroh Sulaswari; AT. Sugeng Priyanto (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACTThis study aims to determine the social studies teacher's perception of the implementation of the merdeka belajar curriculum and the social studies teacher's perception of social studies learning that is integrated with applied Islamic values through social studies material for MTs. in Kudus. This research is motivated by changes in the merdeka belajar curriculum which has not been accompanied by readiness on the part of the teacher, included in the preparation of teaching materials which are entirely made by the teacher. Researchers used a qualitative descriptive approach by collecting data through interviews and FGDs. Based on the results of the contextual analysis of the research data, it shows that 30 social studies teachers MTs in Kudus who are members of the MGMP IPS MTs of Kudus Regency have known about the change in curriculum to become an merdeka belajar curriculum even though they were not fully prepared for its implementation. Teachers feel they are not ready to face curriculum changes related to the learning and evaluation process. The results also found that social studies teachers understand the importance of integrating Islamic values in social studies learning through the development of social studies teaching materials. Merdeka belajar curriculum is considered more flexible and focuses on essential material so that the material is not too dense. Social studies teachers allow it to develop materials with the characteristics of the school environment and students, including incorporating Islamic values into learning materials.Keywords: Merdeka belajar Curriculum, Social Studies Learning, Islamic Religious Values, Integration of Science and Religion.Â Â